Determinan Pertumbuhan Ekonomi di Provinsi Sulawesi Tenggara - Rizky Dwi Alyani (PPJP ULM, 2024)
Economic growth can be an indicator that reflects how advanced and prosperous the condition of a region can be influenced by various aspects. This study attempts to analyze the determinants of economic growth in Southeast Sulawesi Province using the identified factors, which include: (1) poverty percentage, (2) population density per km2, (3) average years of schooling, and (4) life expectancy. The research used fixed effect model estimation with panel data of 17 districts/cities in Southeast Sulawesi during 2019-2023. Based on the results of the analysis, it was found that the percentage of poverty, population density, average years of schooling, and life expectancy (AHH) simultaneously and significantly affect economic growth in Southeast Sulawesi Province. Economic growth is significantly influenced by the percentage of poverty rate, average years of schooling, and life expectancy rate (AHH). Meanwhile, population density has no significant effect on economic growth in Southeast Sulawesi. The limitation of this study is that the independent variables in the study were only able to explain 16,7 percent. For future research, the determinants of economic growth in Southeast Sulawesi can be tested by adding other variables.